Upaya Peningkatan Volume Cairan Tubuh Pasien Post Laminectomy Lumbal - MUTHMAINNAH, QOWIYATUL; , Okti Sri Purwanti, S. Kep, Ns, M. Kep, Ns. Sp. Kep. MB; , Fahrun Nur Rosyid, S.Kep., Ns., M.Kes (2017)
Background: spinal cord injury is one of the most serious health problems that can result in permanent disability until death. A fast and precise handling needs to be given in the case of spinal cord injury, one surgery. Laminectomy is in the form of excision surgery and the posterior branch of the spinous process of the vertebra. In January 2017 at the ICU of a hospital, there were 13 cases of laminectomy surgery. Surgery resulted in trauma to the tissue that can lead to an imbalance of body fluids. Bleeding is the impact of the surgery, and can lead to loss of fluid volume (dehydration). So it needs an effort to increase the volume of rehydration fluids in the body or in patients with postoperative laminectomy. Objective: provide an overview of efforts to increase the volume of body fluids in patients in the ICU post laminectomy sugery of a hospital. Methods: The method used is descriptive case study in patients post laminectomy surgery in hospital on 22 to 24 February 2017. The data was collected using nursing care author by way of assessment, patient medical records, interview, physical examination. After the data collected then analyzed the problem, formulate a care plan, implement care to patients, and evaluate the results. Results: The patients showed an increase in body fluid volume, as evidenced by increased fluid balance of -300 ml to +95 ml, lip mucosa moist, fairly common situation after efforts to blood transfusions, intravenous or parenteral fluid fulfillment, fulfillment oral intake, and calculation of fluid balance , Conclusion: The lack of fluid volume problem is resolved in part because patients still felt a bit weak / weak is reduced. Suggestion: recommended to the patients and families to improve oral intake independently.